2021
DOI: 10.3389/fnagi.2021.632374
|View full text |Cite
|
Sign up to set email alerts
|

Dl-3-n-Butylphthalide Alleviates Demyelination and Improves Cognitive Function by Promoting Mitochondrial Dynamics in White Matter Lesions

Abstract: White matter lesions (WMLs) are a type of cerebrovascular disorder accompanied by demyelination and cognitive decline. Dl-3-n-butylphthalide (D1-NBP) is a neuroprotective drug used for the treatment of ischemic cerebrovascular diseases, although the function of DI-NBP on WML is still not clear. This study aims to investigate whether DI-NBP affects cognitive function and ameliorates demyelination in a model of WML. The bilateral carotid artery stenosis (BCAS) mouse model and in vitro brain slice cultures with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Drug concentrations were chosen based on previous reports. Some previous studies give us a clue on employing the experimental concentration of NBP ( 43 , 47 ). Combined with our pilot study, 50 mg/kg (low) and 100 mg/kg (high), the two comprehensive considerations were applied in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug concentrations were chosen based on previous reports. Some previous studies give us a clue on employing the experimental concentration of NBP ( 43 , 47 ). Combined with our pilot study, 50 mg/kg (low) and 100 mg/kg (high), the two comprehensive considerations were applied in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Dl-3-n-butylphthalide (NBP), has been approved for the therapy of acute ischemic stroke in patients since 2002 in China (36)(37)(38). Recently, studies have shown that NBP holds extensive pharmacological activities (39)(40)(41)(42)(43)(44)(45) and may exert potentially therapeutically beneficial effects on ischemia and vascular dementia; however, its precise mechanisms remain unclear. Evidences have suggested that NBP treatment could exert neuroprotective actions by enhancing anti-oxidation and attenuating mitochondrial dysfunction in models of ischemic stroke and could inhibit NLRP3 inflammasome activation via upregulating Nrf2 in AD models (45,46).…”
Section: Introductionmentioning
confidence: 99%
“…Enlarged and swollen mitochondria are observed in axons, accompanied by fading cristae in the mitochondria ( Coughlin et al, 2015 ; Thai et al, 2019 ). Mitochondrial dysfunction impairs mitochondrial transport along the axons and triggers necrosis of neurons ( Chandrasekaran et al, 2019 ; Feng et al, 2021 ). Some RGCs have an intact cell membrane with swollen organelles; some RGCs are severely damaged with disrupted cytoplasmic organelles and electron-dense clumped nuclear remnants distributed in the cytoplasm ( Narciso et al, 2001 ).…”
Section: The Phenomenon Of Demyelinationmentioning
confidence: 99%
“… Classification Drug Mechanism Ref. Improve mitochondrial energy metabolism Vitamin E, vitamin C, alpha-lipoic acid, MitoQ, curcumin, astaxanthin, ginkgo biloba preparations Reduce superoxide radicals and scavenge hydrogen peroxide [ [83] , [84] , [85] , [86] ] Cyclosporin A mPTP inhibitor [ 87 ] Nicardipine Calcium channel blocker [ 64 ] sodium rutin Enhances the level of mitochondrial oxidative phosphorylation [ 89 ] Batrachocholine Improve mitochondrial ATP metabolism and modifying antioxidant proteins [ 90 ] Ginsenoside R b1 Inhibition of mitochondrial complex I activity [ 91 , 92 ] Balance the mitochondrial dynamics Mdivi-1 Repairs mitochondrial breakage and distribution defects [ 76 ] SS-31 Acts on the cardiolipin of mitochondrial inner membrane [ 93 , 94 ] Butylphthalide Balances the mitochondrial dynamics [ 95 ] Coordinate mitochondrial quality control Rapamycin, Torin1 and niclosamide Downregulation of the mTORC1 pathway [ 96 ] …”
Section: Drugs For Maintaining Mitochondrial Homeostasis In Admentioning
confidence: 99%